Analysis Of Financial Performance of Tourism Sector Company Before and During The Covid-19 Pandemic - Tenan, Memet; Sunaryo, Kunti; Yulianti, Retno (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
This study aims to analyse of financial performance of the hotel, restaurant and tourism sub-sectors listed on the Indonesia Stock Exchange (IDX) before and during the Covid-19 pandemic. Financial performance is measured by using the ratio of liquidity, solvency, activity and profitability. The data used are secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) in 2018-2021. The population of this study is 38 companies and the number of research samples is 26 companies, which were obtained through purposive sampling in 2018-2021. The analytical method used is descriptive statistical test, data normality test, and Wilcoxon signed rank test. The results of this study show that there are differences in the liquidity ratio (CR), solvency ratio (DER), activity ratio (TATO), and profitability ratio (ROA) of hotel, restaurant and tourism subsector companies that listed on the Indonesian Stock Exchange between before and during the Covid-19 pandemic.